The Qur’anic Approach to Purification: Verses Punishing Adultery as an Example - Hamdan, Sawsan Arafat Musa (Dirasat: Shari’a and Law Sciences, 2024)
Objectives: The research aims to explain the Quran’s approach to purification through verses punishing adultery as an example by reviewing the starting points of the study and revealing its characteristics. Methods: The study followed inductive study methods, extrapolating texts on the adultery limit, analyzing statements from interpreters, and extracting features of the Quranic approach to cleansing from adultery. Results: The study defined the Quranic approach to purification from adultery as the legislation governing life’s domains and its implementing mechanisms in the Qur’an, aiming to achieve human idealism through modification and cleansing of adultery and its precursors. Its features are defined by characteristics such as subjecting the limit to legitimate policy, assessing punishment with full grace, considering human interests, ensuring equal application of penalties, and employing cognitive and procedural methods in the Quranic curriculum. Cognitive methods establish righteous rules of faith and employ verbal and semantic prohibition, while procedural methods include excluding reasons instigating adultery, adopting opposite methods to deter spoilers, reinforcing the perpetrator’s sense of remorse, tuning sentiment towards God’s illumination, discharging negative feelings psychologically, and using events in pedagogy. Conclusion: Following the Quranic curriculum in dealing with the challenges of Muslim society is crucial in Islamic education. The text offers practical applications to teach legislators what works for humanity.